Haiti : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
This document presents a profile of poverty, and indicates briefly the stakes and challenges involved, using available quantitative and qualitative data to specify the targeted objectives to be reached. Actions to be taken are then positioned within a macroeconomic framework for which short- and medium-term objectives are specified, together with an outline of sectoral policies. The major sectoral priorities of intervention are outlined. Finally, the paper discusses the strategy to be followed in drawing up the full Poverty Reduction Strategy Paper (PRSP).